STUDI TENTANG PEMBELAJARAN KESENIAN KARUNGUT DAYAK NGAJU SISWA TUNANETRA DI SLB NEGERI 1 PALANGKARAYA - Mahmudah, Istiyati; Yanti, Melda Yuli; Andini, Seli Pramudita; Astuti, Yulia (Universitas Tanjungpura, 2023)
Children with special needs are children who have special personalities such as blind people where children experience disturbances or limitations in their sense of sight. The arts that many blind children are involved in are music and sound arts because these two arts do not prioritize the sense of sight. Art that is suitable for blind children to study is the Dayak Ngaju sack art which is implemented at SLB Negeri 1 Palangkaraya. This study aims to describe the use of methods by art teachers in teaching, the media used during the process of learning the Dayak Ngaju sack art and the factors that support and hinder the learning of sack art at SLB Negeri 1 Palangkaraya. This study uses a descriptive qualitative approach. The results showed that art teachers used three methods when teaching, namely lecture, demonstration and repetition methods. The media used by the art teacher in the sack art at SLB Negeri 1 Palangkaraya are harps, drums, gongs and special braille tools used by blind children to assist during the learning process. The supporting and inhibiting factors themselves are in the students and the teacher. The learning of the Dayak Ngaju sack art at SLB Negeri 1 Palangkaraya has been well implemented. This is evident from the variety of methods used by the teacher when teaching, the success of the teacher in increasing the interest and enthusiasm of students when the learning process takes place and also seen from the students' mastery of singing the sackcloth song and playing the sackcloth accompaniment.